1995
DOI: 10.1093/nar/23.21.4239
|View full text |Cite
|
Sign up to set email alerts
|

Binding of phosphorothioate oligodeoxynucleotides to basic fibroblast growth factor, recombinant soluble CD4, laminin and fibronectin is P-chirality independent

Abstract: Antisense oligodeoxynucleotides can selectively inhibit the expression of individual genes and thus have potential applications in anticancer and antiviral therapy. A critical prerequisite to their use as therapeutic agents is the understanding of their non-specific interactions with biological structures, e.g. proteins. In this study we examined the interactions of P-chiral phosphorothioate oligodeoxynucleotides with several proteins. The Rp- and Sp- diastereomers, and racemic machine-made mixtures, or M-olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…S-oligos act as heparin mimetics and they bind to heparin binding proteins such as bFGF (Benimetskaya et al, 1995). Furthermore, S-oligos inhibit HIV-1 DNA integration (Matsukura et al, 1987;Agrawal et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…S-oligos act as heparin mimetics and they bind to heparin binding proteins such as bFGF (Benimetskaya et al, 1995). Furthermore, S-oligos inhibit HIV-1 DNA integration (Matsukura et al, 1987;Agrawal et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Marshall et al (1992) reported that the inhibitory effect of oligonucleotides on HIV-1 reverse transcriptase could be at least 30-fold greater with phosphorodithioate oligonucleotides, which have two sulphur at each site of internucleotide linkages, than with phosphorothioate oligonucleotides. Benimetskaya et al (1995) reported that binding of phosphorothioate oligonucleotides to proteins is independent on P-chirality at the internucleotide linkage sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations